The Representation of Ethiopian History in Secondary School History Textbooks (1979-2000) - Workye, Yimegnutal Nibret; Baye, Temesgen Gebeyehu; Addam, Geremew Eskezia (Ethiopian Journal of Social Sciences, 2025)
The main purpose of this study is to analyze the representation of Ethiopian history in secondary school history textbooks from 1979, with a focus on the Derg regime (1974–1991) and the early years of the EPRDF until 2000. Using qualitative content analysis of textbooks, curricula, and educational policy documents, the study reveals a history education shaped to align with socialist ideology, emphasizing class struggle while vilifying the pre-revolutionary periods of Ethiopia. Significant historical achievements, such as the Victory of Adwa, were undermined, promoting discord among people instead of fostering unity. The textbooks prioritized global socialist narratives over Ethiopian history, distorting events, excluding significant periods, and disregarding contributions of modern Ethiopian leaders such as Emperor Menelik II and Haile Selassie I. Moreover, the Marxist history curriculum relegated its role of fostering national cohesion and critical thinking by neglecting Ethiopian history and its unifying power.Keywords: Community cohesion, History education, Marxist historiography, Objectivity, State ideology